Frequency of Causative Factors and Microbial Etiology of the Keratitis - Nisar Ahmed Khan, Narain Das, Asma Shams, Humaira Ashraf, Riaz Ahmed Memon, Abdul Haq Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of the causative factors and most common organisms of keratitis. Materials and methods: This descriptive cross- sectional study was conducted at the Ophthalmology department of Indus Medical College Tando Muhammad Khan. The study included both male and female patients diagnosed with microbial keratitis between the ages of 17 and 60 years. Slit lamp bio microscopy of the anterior segment was performed on all patients, and the corneal epithelial defect was quantified in millimeters using the slit lamp. Corneal scrapings were collected from the base of ulcer using a bent tip 26-gauge hypodermic needle under topical anaesthetic (Alcain), and the sample was immediately studied under an electron microscope, confirming the diagnosis of bacterial keratitis. Patients were then hospitalized, and at the conclusion of therapy, their healing was examined. The research proforma was used to gather all the data, and SPSS version 26 was applied for data analysis. Results: A total of 70 cases diagnosed with microbial keratitis were studied with an average age was 38.22+7.81 years and males were in majority 65.7%. A majority of the patients 55.7% were poor socioeconomically, followed by 32.9% had middle socioeconomic status and only 11.4% were rich socioeconomically. Contact lens and trauma were commonest factors as 28.6% and 24.3% respectively, followed by a history of steroid 11.4%, past ocular previous surgery 11.4%, ocular surface illness 14.3% cases, and others10.0%. Bacterial and fungus keratitis were commonest 55.7% and 27.1% respectively, followed by 12.9% viral keratitis, mixed microbial keratitis was 2.9% and only one case had Acanthamoeba keratitis. Conclusion: This study concludes that rural areas’ poor young males were highly affected by the microbial keratitis. Trauma and unhygienic lens wear were observed to be the prevalent causative factors, with highly prevalent bacterial and fungal microbial etiology.